NurfürdenpersönlichenfürStudien,Forschung,zukommerziellenZweckenverwendetwerden不等式5X-2≥3(X+1)3x(x+5)>3x2+7x-4<2x+13x+14>4(2x-9)3x-7≥4x-42x-3x-3<(x-1)≥--4<2x+12x-6<x-23×10x<5007(X+3)>982x-3x+3<62x-3x+1<62x-3x+3<12x-19<7x+313x-2(9-x)>3(7+2x)-(11-6x)2(3x-1)-3(4x+5)≤x-4(x-7)2(x-1)-x>3(x-1)-3x-515-(7+5x)≤2x+(5-3x)4(2X-3)>5(X+2)2X+4<05X-2≥3(X+1)2(X-3)≤45m-3>02x-3(x-1)>66x-3(x-1)≤12-2(x+2)3(1-3x)<4(x-1)8-7x+1>2(3x-2)3x+14>4(2x-9)3-3m<-2m5x+3x>2-3y+9<7(3+8)x>65-3/1x>511x-5x>3-3a-9a>11-4a+9>633x+33<15b-9<9b6x+8>3x+83x-7≥4x-42x-19<7x+-2(9-x)>3(7+2x)-(11-6x).2(3x-1)-3(4x+5)≤x-4(x-7).2(x-1)-x>3(x-1)-3x-[y-2(y-7)]≤-(7+5x)≤2x+(5-3x).3*10(x+1)>5007(x+3)>988-7X>4-5X2(1+X)>3(X-7)4(2X-3)>5(X+2)3x-2(9-x)>3(7+2x)-(11-6x)2(3x-1)-3(4x+5)≤x-4(x-7)2(x-1)-x>3(x-1)-3x-53[y-2(y-7)]≤4y15-(7+5x)≤2x+(5-3x)20x-3≤5x+(x-5)7x-2(x-3)<163(2x-1)<4(x-1)5-x(x+3)>2-x(x-1)3-4[1-3(2-x)]>594x-10<15x-(8x-2)3(6+x)>6(X+3)2/3(x+6-9)<5(-x+9)3x(x+5)>3x2+73x+14>4(2x-9)3x-7≥4x-42x-3x-3<(x-1)≥-(X+3)>982x-3x+3<62x-3x+1<62x-3x+3<12x-19<7x+313x-2(9-x)>3(7+2x)-(11-6x)2(3x-1)-3(4x+5)≤x-4(x-7)2(x-1)-x>3(x-1)-3x-515-(7+5x)≤2x+(5-3x)4(2X-3)>5(X+2)5X-2≥3(X+1)2(X-3)≤45m-3>02x-3(x-1)>66x-3(x-1)≤12-2(x+2)3(1-3x)<4(x-1)8-7x+1>2(3x-2)3x+14>4(2x-9)3-3m<-2m6x+8>3x+83x-7≥4x-42x-19<7x+-2(9-x)>3(7+2x)-(11-6x).2(3x-1)-3(4x+5)≤x-4(x-7).2(x-1)-x>3(x-1)-3x-[y-2(y-7)]≤-(7+5x)≤2x+(5-3x).2x-19<7x+313x-2(9
一元一次不等式计算题 来自淘豆网m.daumloan.com转载请标明出处.